Constitutional theory and political history as justification for the gender quota in Egypt's legislature - El-Menshawy, Abir Ahmed (AUC Knowledge Fountain, 2013)
The purpose of this thesis is to examine the conformity of gender quotas with the constitutional concept of equality. The importance of this examination is to answer the question whether gender quotas are constitutional. My argument is that gender quotas are constitutional because they address de facto inequality by making women’s representation equal to men’s representation. I argue that Egypt has a history of adopting quotas to guarantee the representation of disadvantaged groups. I also tie the constitutionality of the gender quota to the current political landscape where the Muslim Brotherhood controls the state. I argue that gender quotas will not, most probably, be adopted under the leadership of the Muslim Brotherhood, as they do not believe in equal representation for women